2014
DOI: 10.1016/j.gien.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of three different irrigation techniques in the removal of smear layer and organic debris from root canal wall: a scanning electron microscope study

Abstract: Aim: Aim of this study was to compare the removal of smear layer and organic debris within the tooth canal among conventional needle irrigation, EndoVac and Endoactivator.\ud Methodology: Eighty single-rooted extracted human teeth were prepared with rotary NiTi instrumentation and randomly separated into 4 groups. Twenty teeth were used as positive control (Group 1), irrigated with only saline. Teeth assigned to Group 2 (n = 20) received irrigation with a conventional syringe and a 30-gauge needle (NaviTip, Ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
2
15
0
1
Order By: Relevance
“…12,13 In the present study, sonic activation systems showed better results than conventional irrigation in debris removal. Although this result is consistent with previous studies that found EndoActivator is more effective 21,22 ; it is in contradiction with the studies which could not find an statistically significant difference in the same subject [23][24][25] . This difference may have been resulted from the lack of irrigation activation with EDTA in two studies.…”
Section: Discussionsupporting
confidence: 68%
“…12,13 In the present study, sonic activation systems showed better results than conventional irrigation in debris removal. Although this result is consistent with previous studies that found EndoActivator is more effective 21,22 ; it is in contradiction with the studies which could not find an statistically significant difference in the same subject [23][24][25] . This difference may have been resulted from the lack of irrigation activation with EDTA in two studies.…”
Section: Discussionsupporting
confidence: 68%
“…Following title and abstract screening, 37 citations were eligible for full-text evaluation of which 16 provided direct comparisons between CNI and IATs, under the aforementioned conditions, therefore qualifying for inclusion ( Table 2). Only 12 of these studies provided sufficient quantitative data to be included into the meta-analysis [Caron et al 2010, R€ odig et al 2010, Saber Sel-D & Hashem 2011, Al-Ali et al 2012, Mancini et al 2013, Ahuja et al 2014, Andrabi et al 2014, C ßapar & Aydinbelge 2014, Castagnola et al 2014, Singh et al 2014, Akyuz-Ekim & Erdemir 2015]. The detailed reasons for rejection of the 21 articles excluded at full-text evaluation are given in Table 3.…”
Section: Studies Selectedmentioning
confidence: 99%
“…However, due to the large anatomical variations of the roots, such as in curved and atresic canals, the ultrasonic tip can touch the walls of the canal, limiting its movement and generating a negative result in the conduction of the ultrasonic energy, besides being able to cause accidents, as uncontrolled removal of dentin, deviation of the original canal pathway, apical obstruction and even root perforation. 24 In the studies of the authors Castagnola et al 34 and Goode et al, 35 the efficacy of the removal of smear layer from root canals using different systems for agitation of irrigation solution was evaluated, which included EndoActivator, EndoVac and conventional irrigation (NaviTip). In both studies the EndoActivator system obtained a better removal of smear layer and organic debris in all thirds of the root canal, especially in the middle and apical third.…”
Section: Discussionmentioning
confidence: 99%